AN INTERVIEW ABOUT SADDLE-MAKING, ONE OF THE TRADITIONAL HANDICRAFTS, IN BOSNIA AND HERZEGOVINA - Yusuf Ziya Sümbüllü; Melinda Botalić (Human Research in Rehabilitation, 2012)
Handicraft products are of great value as material culture products since they have been used during definite times of a society. These products are significant because they will ensure cultural continuity between the past and future. Saaddle-making, a conventional handicraft, is one of these aforesaid culture transmitters of which realm of existence is getting narrow because of developing technology.